A Community Intervention In Covid-19 Pandemic: Occupational Health And Safety For Moslem Online Transportation - Yanwar Arief; Muhammad Rizki Fauji; Robby Fernanda Arifin; Bahril Hidayat (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study was conducted to see the implementation of community intervention the Gojek Online Occupational Health and Safety (OHS) online bike during the coronavirus disease (Covid-19) pandemic in Pekanbaru City, and to provide online bike drivers with psychoeducation interventions. Main data collection by observation to see the introduction of occupational health and safety (OHS) of the Gojek online bike and questionnaires to take a look at the results of the interventions. Results from the observations made by 15 drivers indicate that the application of occupational health and safety (OHS) was 59%. The results of the 15-person questionnaire on the benefits of the intervention given are 81%. Therefore, psychoeducation interventions in the form of posters and digital videos are successful and provide advantages in the implementation of online bike occupational health and safety (OHS) Gojek during the pandemic in Pekanbaru City.